1998
DOI: 10.1253/jcj.62.599
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Effects of a Subdepressor Dose of L-158,809, an Angiotensin II Type 1 Receptor Antagonist, on Cardiac Hypertrophy and Nephropathy Via the Activated Human Renin-Angiotensin System in Double Transgenic Mice With Hypertension

Abstract: he Tsukuba hypertensive mouse (THM) is a hypertensive animal model prepared by introducing human renin and angiotensinogen genes into C57BL/6 mouse. 1 In THM, the cause of hypertension is known to be a single factor, an enhancement of the reninangiotensin system (RAS). In THM, angiotensin II (AII) is 3-5 times higher in serum and that in the heart and kidney is 4-5 times higher compared to C57BL/6 mice. 2 At 6 weeks of age, when blood pressure measurement becomes possible, THM already show elevated blood press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…However, such a remarkably increased hypertension is also due to activation of systemic and local (tissue level) RAS in THM. The previous studies have already reported that local activation of RAS is involved in tissue injuries, because subdepressor dose of an AT1 receptor antagonist prevents cardiac hypertrophy and nephropathy, suggesting that local Ang II is profoundly involved in the phenotypes (Kai et al, 1998a). Furthermore, a serum level of ET-1 in THM was not remarkably elevated compared to the control, and the acute effect of SB209670 was not observed to decrease the higher blood pressure in THM (Maki et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…However, such a remarkably increased hypertension is also due to activation of systemic and local (tissue level) RAS in THM. The previous studies have already reported that local activation of RAS is involved in tissue injuries, because subdepressor dose of an AT1 receptor antagonist prevents cardiac hypertrophy and nephropathy, suggesting that local Ang II is profoundly involved in the phenotypes (Kai et al, 1998a). Furthermore, a serum level of ET-1 in THM was not remarkably elevated compared to the control, and the acute effect of SB209670 was not observed to decrease the higher blood pressure in THM (Maki et al, 1998).…”
Section: Discussionmentioning
confidence: 97%
“…3) THM facilitated pharmacological examination aimed at investigating the role of interaction of two human gene products in BP. Therefore, THM differs greatly from spontaneously hypertensive rats, a widely used model of hypertension with an unclassified genetic background of hypertension, and also differs Ang II-infused rats, in which plasma Ang II level was markedly elevated by Ang II infusion (Herizi et al, 1998;Kai et al, 1998a); however, it remains to be examined whether tissue Ang II level is increased or not in various organs such as the heart and kidney. Therefore, it is likely that the Ang II-infused model demonstrates the action of exogenous Ang II on organs as an endocrine effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…These animals are prone to developing hypertension (13)(14)(15). Kai et al (16,17) observed albuminuria and glomerular sclerosis in 28-week-old THM. Thus, the THM is a useful model of hypertensive nephropathy induced by overproduction of angiotensin II.…”
Section: Introductionmentioning
confidence: 99%